Analisis Elemen Visual Pada Komik “Pupus Putus Sekolah” - Yuliaqanita, Adinda; Amanda, Romauli; Salsabila, Robiah; Khoirunisa, Shafira (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
Digital comics are currently gaining popularity among many people, especially teenagers. Not only serving as a form of entertainment, they can also be utilized as a means of conveying information. The objective of this research is to understand the use of visual elements in conveying messages and information through the comic "Pupus Putus Sekolah." This study employs a descriptive method, illustrating specific situations and describing facts and their relevance to the researched visual elements applied in the comic "Pupus Putus Sekolah" in a factual, detailed, sequential, and precise manner. The research relies on illustrative data, and the data collection technique involves observation or scrutiny of the visual elements used. The researcher utilizes the method of observation, listening, and reading the entire season and episodes of the comic "Pupus Putus Sekolah," noting essential information for data collection. Meanwhile, the analysis involves classifying the collected data into its types, analyzing and interpreting the data, presenting the analyzed data, and drawing conclusions. Based on the conducted analysis, the findings reveal that visual elements such as panels, perspectives, gutters, speech balloons, sound effects, illustrations, story, splash, motion lines, symbolism, and storytelling play a crucial role in influencing how the comic's narrative content is conveyed.